Pancasila and Transnational Ideology in the Maqāṣid al-Sharī‘ah Perspective - Yasid Yasid; Makhshushi Zakiyah; Moh. Asra (Islamica: Jurnal Studi Keislaman, 2021)
This article seeks to explore the importance of maqāṣid al-sharī‘ah as a theory to address the develop-ment of Islamic law in the contemporary world. Following the need to respond to modern challenges in Muslim society, the theory of maqāṣid al-sharī‘ah needs to be worked out optimally so that the results of legal provisions do not shift from the primary objectives of the state and government formation. The fundamental goal is to create benefits for the nation and state. The trend of the emergence of nation-states with multi-ethnic, multi-racial, multi-cultural, even multi-religious populations demands the need for tools for sophisticated religious analysis such as the theory of maqāṣid al-sharī‘ah. In the context of a nation-state like Indonesia, maqāṣid al-sharī‘ah can be used as a theoretical perspective to determine the legal standing of the debate about Pancasila and transnational ideology, which has recently been widely discussed in the community. Pancasila is an agreement of the Indonesian founding fathers to maintain the unity and integrity of the nation amidst the diversities. This article describes the role of maqāṣid al-sharī‘ah in the study of the Islamic constitutional law, the dynamics of Islamic law, and the Pancasila as ideology of the state.